Synthesis, Characterization, and Antibacterial Activities of 1H-Imidazo [5, 6-f] [1,10] Phenanthroline-2(3H)-Thione and Its Ni(II) and Cu(II) Complexes - Radiet Anbessie Tirkeso; Tilahun Wubalem Tsega; Gebru G/Tsadik Amdemichael (Journal of Chemistry)
As multidrug resistant pathogens are emerging, the search for novel potent drug candidates is ever going. Heterocycles are known by their broad spectrum of biological activities, so a search for a new drug from heterocycles can elevate the chance of success. The aim of this study was to obtain novel potent antimicrobial compounds. In line with this, 1H-imidazo [5, 6-f] [1,10] phenanthroline-2(3H)-thione and its complexes (Ni(II) and Cu(II)) were synthesized, characterized, and evaluated against bacterial strains. The compounds were characterized by elemental analyses (C, H, N, and S), FT-IR, 1H-NMR, 13C-NMR, AAS, UV-Vis spectra, and molar conductivity measurement. The results showed that the ligand is bidentate, and the molar conductivity measurement indicates that complexes are electrolytic. Electronic spectral study showed octahedral and distorted octahedral geometry for the Ni(II) and Cu(II) complex, respectively. The ligand and its complexes were screened against four bacterial strains using disk diffusion method. The result revealed that the Ni(II) complex showed more bioactivity than gentamicin against Staphylococcus aureus and Escherichia coli, while the Cu(II) complex is more active than the Ni(II) complex against Bacillus subtilis. Both Cu(II) and Ni(II) complexes exhibit higher antibacterial activities than the free ligand.